Diagnosis and treatment evaluation in patients with spontaneous intracranial hypotension - Mehta, Dwij; Cheema, Sanjay; Davagnanam, Indran; Matharu, Manjit (Frontiers in Neurology, 2023)
Spontaneous intracranial hypotension is characterised by an orthostatic headache and audiovestibular symptoms alongside a myriad of other non-specific symptoms. It is caused by an unregulated loss of cerebrospinal fluid at the spinal level. Indirect features of CSF leaks are seen on brain imaging as signs of intracranial hypotension and/or CSF hypovolaemia as well as a low opening pressure on lumbar puncture. Direct evidence of CSF leaks can frequently, but not invariably, be observed on spinal imaging. The condition is frequently misdiagnosed due to its vague symptoms and a lack of awareness of the condition amongst the non-neurological specialities. There is also a distinct lack of consensus on which of the many investigative and treatment options available to use when managing suspected CSF leaks. The aim of this article is to review the current literature on spontaneous intracranial hypotension and its clinical presentation, preferred investigation modalities, and most efficacious treatment options. By doing so, we hope to provide a framework on how to approach a patient with suspected spontaneous intracranial hypotension and help minimise diagnostic and treatment delays in order to improve clinical outcomes.